Analysis of the Circular Economy's Implementation at Maggot House Mengger Sub-District Bandung City - Rochaeni, Anni; Ardianti, Dhini; Suryana, Popo; Ardiani, Winda P.; Habibie, Panji A.; Fadhlan, M. Razkia; Nurnazmi, Alvi; Syahrani, Aura P (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
In 2023, the city of Bandung faced serious problems because the Sarimukti landfill caught fire and the city of Bandung experienced a